ANALISIS PENGARUH BUDAYA ORGANISASI TERHADAP KINERJA DAN KEPUASAN CIVITAS AKADEMIKA POLTEKKES KEMENKES SEMARANG - Hermien Nugraheni; Supriyadi Supriyadi; Sadimin Sadimin (Jurnal Kesehatan Gigi, 2016)
TITLEAnalysis of organization-practice effect toward performance and satisfaction of Poltekes Kemenkes Semarang civitas academicABSTRACTOrganizational culture in Health Polytechnic of Semarang to implementation for college’s quality assurance system would guide the academic community of Health Polytechnic Semarang about how a job is well done and what is important. The aim of this study is to analyze the influence of organizational culture on the performance and satisfaction of the academic community in Health Polytechnic Semarang to implementation of College’s Quality Assurance System.The method used to collect data in this study is a survey method. The research design used for user satisfaction survey of graduates is a cross -sectional (cross-sectional). The research variabels include: Organizational Culture , Academic Community Performance and Satisfaction in the implementation of College’s Quality Assurance System in Health Polytechnic Semarang and stakeholder satisfaction about Health Polytechnic Semarang’s graduate.The results showed that most respondents performs well and satisfied with the implementation of the College’s Quality Assurance System. Stakeholder satisfaction levels for Health Polytechnic Semarang graduates are in the category of "enough". With components that the highest satisfaction level in the integrity and the lowest on self-development component. Organizational culture variables that affect performance are: innovation and the courage to take risks, attention to detail things, people orientation, and stability, as well as the most influential are: stability. Variable organizational culture that influence satisfaction is the attention to detail matters, people orientation, and stability, while the most influential is the attention to detail matters. Key words : organizational culture , performance, satisfaction